MANAGEMENT OF RISK IN DELIVERING COMPLEX RESEARCH AND DEVELOPMENT PROJECTS - Alshehhi, Badr (Archives of Business Research, 2018)
Engineering Doctorate Research THESIS Management of Risk in Delivering Complex Research and Development Projects: A Case of the Research & Development Center of the United Arab Emirates Armed Forces Badr Alshehhi a, Dr. David Thorpe b, Dr. Steven Goh c, Dr. Sultan Alkaabi d a University of Southern Queensland, Toowoomba, Australia w0061492@umail.usq.edu.au b University of Southern Queensland, Springfield, Australia david.thorpe@usq.edu.au c University of Southern Queensland, Toowoomba, Australia Steven.Goh@usq.edu.au d University of Southern Queensland, Toowoomba, Australia sultan.a.alkaabi@gmail.com Abstract Risk management continues to be a major feature of the project management of large construction, engineering, technological, and research and development projects in an attempt to reduce uncertainties and to achieve project success. There are uncertainties and risks at every stage of R&D projects through the product lifecycle. Therefore, management of the risks is an important challenge for the R&D project managers, and the close linking of project risk management with the success of the project is acknowledged across the world. Thus, the focus of this study is on the management of risk in delivering complex research and development projects within the United Arab Emirates Armed Forces. Even though the management of risks related to the military environments has been studied for several years, studies on the risks pertaining to research and development of the military environments are still comparatively low and almost negligible in the UAE. This gives value to such type of study for filling in the literature. This chapter highlights the research purpose, objectives, questions, problem statement, and motivation together with implication of the research to theory and the wider community of practice.